ChemInform Abstract: Potassium Iodide/tert‐Butyl Hydroperoxide‐Mediated Oxidative Annulation for the Selective Synthesis of N‐Substituted 1, 2, 3‐Benzotriazine‐4(3H)‐ones Using Nitromethane as the Nitrogen Synthon. Issue 22 (12th May 2016) - Yan, Yizhe; Niu, Bin; Xu, Kun; Yu, Jianhua; Zhi, Huanhuan; Liu, Yanqi
Abstract: The novel oxidative annulation of 2‐aminobenzamides with nitromethane is advantageous with regards to high chemoselectivity, operational simplicity and good functional group tolerance.